145k views
3 votes
Examine (a), (b), and (c) and select the correct answer.

(a) 11 - ( 6 + 3 )
(b) ( 8 - 2 ) - 3
(c) 12 - ( 5 - 4 )

a. (a) + (b) = (c)
b. (c) - (b) < (a)
c. (b) > (c)
d. (c) > (a) + (b)

(Explanation would be appreciated)

User John Jones
by
5.5k points

1 Answer

2 votes

First: solve the expressions

(a) 11-(6+3)= 11-9= 2

(b) (8-2)-3= 6-3=2

(c) 12-(5-4)=12-1=11

Next: plug them in to the choices

a. (2)+(2)=11 (this is not true so this is wrong)

b. (11)-(2)<2 (this is not true so it is wrong)

c. (2)>(11) (this is not true so this is wrong)

d. (11)>(2)+(2) (this is true so this is your answer)


your answer is D... Hope this helps :)

User Ase
by
6.3k points